Remedial Measures of Negative Effects of Digital Technology on Conjugal Relationship in Islamic Perspective - Dr. Munazza Sultana; Dr Syed Abdul Ghaffar Bukhari (Al Manhal Research Journal, 2024)
We have entered an era of enhanced digital connectivity where people are connected through social media and latest technology. The increase in the use and the accessibility allows humans to engage and disconnect easily. This technology is not only used in workspaces but also being used in everyday social relationships. The impact of technology use on conjugal relationships are also being affected. Its impact is yet to be explored in Pakistan as the use is increased in metropolitan areas. This study investigates the use of mobiles, television, laptops, and social media platforms as how this negatively impacts on an individual’s sense of security, control as well as attachment. It explores the extent to which couples are addicted to social media and the latest technology in order to interact with each other and the society instead of face to face communication. The study is qualitative in nature to have in-depth examination of the potential negative impacts of technology on intimate couple relationships. And also finds remedial measures, suggested by Islam, in order to reduce the negative impact and save conjugal relationships.